2006
DOI: 10.1016/s1808-8694(15)31013-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Streptococcus pyogenes as an oropharynx colonizer in children attending daycare: a comparative study of different regions in Brazil

Abstract: These results show that daycare attendance is a risk factor for oropharyngeal streptococcal colonization; this was seen in different populations, but was statistically significance in only one of the two samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 8 publications
0
14
0
1
Order By: Relevance
“…The persistently high morbidity–mortality due to RHD in Brazil, with high-cost procedures to treat valvular sequelae, warrant procedures to improve primordial prevention (housing, hygiene), primary prevention prophylaxis (sore-throat treatment), secondary prevention prophylaxis, early diagnosis of asymptomatic rheumatic carditis and tertiary prevention (drugs for HF, valve surgery, anticoagulation) 36. Also, research should examine the factors associated with RHD such as the organism (group A streptococci), genetics and host and environmental factors (socioeconomic status, living conditions, overcrowding, urbanisation, day care,32 nutrition and access to medical services). The World Health Organization has recommended secondary prophylaxis, most effectively delivered within a coordinated programme using a registry of patients60; however, most developing countries still do not have a secondary prophylaxis programme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The persistently high morbidity–mortality due to RHD in Brazil, with high-cost procedures to treat valvular sequelae, warrant procedures to improve primordial prevention (housing, hygiene), primary prevention prophylaxis (sore-throat treatment), secondary prevention prophylaxis, early diagnosis of asymptomatic rheumatic carditis and tertiary prevention (drugs for HF, valve surgery, anticoagulation) 36. Also, research should examine the factors associated with RHD such as the organism (group A streptococci), genetics and host and environmental factors (socioeconomic status, living conditions, overcrowding, urbanisation, day care,32 nutrition and access to medical services). The World Health Organization has recommended secondary prophylaxis, most effectively delivered within a coordinated programme using a registry of patients60; however, most developing countries still do not have a secondary prophylaxis programme.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the different strains of streptococci infecting a population of different genetic backgrounds and the influence of environmental factors 31. The prevalence of Streptococcus pyogenes may differ among Brazilian regions 32. Epidemiological features of group A Streptococcus from a paediatric population were very different in Belgian in comparison with a Brazilian city, not only in its clinical presentation, but also in its genetic diversity and distribution of emm patterns 33.…”
Section: Valvular Heart Diseasementioning
confidence: 99%
“…6 13 Rekürran enfeksiyona yol açabilen AGBHS ta-fl›y›c›l›¤›n› önlemeden, bulafl› engellemek kolay de¤ildir. 5,11,15,16 Ülkemizde, görünürde sa¤l›kl› çocuklardaki AGBHS tafl›y›c›l›¤› için farkl› s›kl›klar bildirilmifltir: Tafl…”
unclassified
“…reported substantially higher rates of S. pyogenes carriage in children attending group child care than in children who did not attend group care (8% vs. 2%, p = 0.02 in one city, 24% vs. 16% in a second city, p = 0.015) (Vieira 2006).…”
Section: Other Bacterial Pathogensmentioning
confidence: 96%
“…Studies conducted in Finland and Brazil reported S. pyogenes carriage rates in children attending group care of 2%, 8%, and 24% (Kontiokari 2005, Vieira 2006). Vieira et.…”
Section: Other Bacterial Pathogensmentioning
confidence: 99%